Anesthesia Management For A Patient With Morbid Obesity Undergoing Laparoscopic Cystectomy And Hysteroscopic Tubal Patency Procedures: A Case Report - Lusyana*, Lya; Parami, Pontisomaya; EM, Tjahya Aryasa (Riwayat: Educational Journal of History and Humanities, 2023)
The laparoscopic surgical procedure has been proven to be highly useful for surgeries in narrow body cavities, such as pelvic surgeries. Performing laparoscopy on morbidly obese patients in the supine, lithotomy, and Trendelenburg positions during surgery presents a challenge in obstetric anesthesia. The patient is a 31-year-old female with a left dermoid ovarian cyst. During the perioperative period, the patient presented with morbid obesity (BMI of 45 kg/m2), and an intermediate risk of obstructive sleep apnea. Perioperatively, arterial blood gas analysis (ABGA) was performed to determine whether there were any ventilation issues typically associated with obesity (i.e.,Pickwickian syndrome). The ABGA results were within normal limits, with a pCO2 of 38 mmHg. General anesthesia was administered, and the patient was induced with 150 mcg of fentanyl, 150 mg of propofol, and 40 mg of atracurium. The surgery was completed without significant hemodynamic changes. After the surgery, the patient was transferred to the Intensive Care Unit for observation in case of any anesthesia-related complications. In conclusion, pre-anesthesia preparation and clear and effective intraoperative communication are crucial in managing a patient with morbid obesity undergoing laparoscopic cystectomy, hysteroscopy, and tubal patency procedures.